2. Kirgistan w pętli energetycznej – problemy z wykorzystaniem potencjału wodnego republiki, tradycyjne i nowe źródła energii .......... 105 - Kosowska, Katarzyna (Kirgistan – oblicza transformacji, 2020)
KYRGYZSTAN IN THE ENERGY LOOP – PROBLEMS USING THE WATER POTENTIAL OF THE REPUBLIC, TRADITIONAL AND NEW ENERGY SOURCESEnergy is one of the most important sectors of Kyrgyzstan’s economy. The energy sector of the republic consists of two segments: oil and gas sector and electricity sector. Hydropower is the dominant area of the Kyrgyz energy sector, which is associated with the huge resources of water energy possessed by Kyrgyzstan. In the future, hydropower could become a guarantee of improving the energy and economic security of Kyrgyzstan. To make it happen, there is a need to solve major problems such as underinvestment in the sector, the need to modernize infrastructure, change pricing policy, and fight corruption. In turn, Kyrgyzstan’s oil and gas sector is controlled by Russian capital (such as Gazprom or Rosneft).